Analisis Kompetensi Profesional Guru PAUD Yang Belum Bersertifikasi PPG - Alya Lathifa; Arjum Atrianis; Norhidayah; Rizky Nabila Harahap; Rita Kurnia (Alzam: Journal of Islamic Early Childhood Education, 2025)
Abstract: This study aims to identify the obstacles faced by Early Childhood Education (PAUD) teachers at Pembina 2 Pekanbaru State Kindergarten in participating in the Teacher Professional Education (PPG) certification program and to analyze its impact on the development of teachers' professional competencies. The competencies examined include learning practice skills, assessment, classroom management, and the use of learning media. This study uses a qualitative approach with a descriptive design. Data collection techniques were carried out through structured observations and in-depth interviews selected purposively with PAUD teachers, school principals, and education supervisors. Interview data were analyzed using thematic analysis through theme identification and cross-source triangulation. The results of the study indicate variations in the level of readiness and competency between certified and non-certified teachers. These differences are influenced by factors such as access to training, time constraints, costs, and institutional policies. The implications of the study emphasize the importance of expanding access to training, professional mentoring programs, and more inclusive portfolio development guidelines. The conclusions of this study emphasize the need to strengthen professional development pathways for non-certified PAUD teachers to support the improvement of the quality of early childhood education services in public schools.